Pengaturan tentang Pembatasan Hak Kebebasan Berekspresi pada Media Sosial dalam Perspektif Hukum Nasional - Wisanjaya, I Gede Pasek Eka; Widodo, Putri Bella Rosy (Jurnal Legislasi Indonesia, 2024)
As part of fundamental human rights, the right to freedom of expression is neither absolute nor unlimited; however, there are restrictions on exercising the right in the context of the democratic rule of law. Presently, the exercise of the right to freedom of expression in social media has been misused by the emergence of fake news or information (hoaxes). The restrictions to exercising the right, as stipulated under the Indonesian national law, are aimed at respecting and protecting the dignity of individuals or other people, and protecting the public interest and national security. This article aims to discuss the impact of entities outside Indonesian sovereignty (jurisdiction) on implementing legal norms restricting the exercise of the right to freedom of expression in social media and the effectiveness of the norms under Indonesian national law. The method used is normative legal research using statutory, cases, and facts approaches. The analysis shows that restrictions on exercising the right to freedom of expression on social media under Indonesia’s national sovereignty have not been fully effective due to the entities of social media platforms outside the territory of Indonesia, which is not may be entirely located or subject to the scope of national jurisdiction.